Public Emotional and Coping Responses to the COVID-19 Infodemic: A Review and Recommendations - Ying, Weijun; Cheng, Cecilia (Frontiers in Psychiatry, 2021)
Since its onset in early 2020, the COVID-19 pandemic has adversely affected not only the physical but also the mental health of people worldwide. Both healthcare professionals and laypersons have sought to learn more about this novel and highly transmissible disease to better understand its etiology, treatment, and prevention. However, information overload and misinformation related to COVID-19 have elicited considerable public anxiety and creating additional health threats. Collectively, these problems have been recognized by the World Health Organization as an “infodemic.” This review provides an overview of the challenges posed by the COVID-19 infodemic globally, using the psychological entropy model as a guiding framework to explicate the potential causes of the infodemic and possible solutions to its resultant problems. We first examine the role of anxiety in information processing and then delineate the adverse impact of the infodemic on various public health issues. Finally, we propose some strategies to combat the infodemic at the public, community, and individual levels.